Corporate Governance dalam Memoderasi Profitabilitas terhadap Agresivitas Pajak : Studi pada Perusahaan Manufaktur di Bursa Efek ASEAN - Suyanto, Suyanto; Pratama, Yhoga Heru; Ellysta, Crissyen Deara; Listyawati, Reni (Jurusan Akuntansi Fakultas Ekonomi Universitas Siliwangi, 2025)
This research aims to evaluate the impact of profitability on tax aggressiveness, with corporate governance acting as a moderating variable. Profitability is assessed using Return on Assets (ROA), while corporate governance is quantified by the number of board members. The study analyzes data from 791 registered manufacturing firms across ASEAN countries from 2018 to 2023. A panel data regression approach employing a fixed effect model is utilized for analysis. The findings indicate that profitability negatively influences tax aggressiveness, suggesting that companies with greater profitability are more inclined to meet their corporate tax obligations. Additionally, corporate governance strengthens the connection between profitability and tax aggressiveness, with factors such as the presence of an independent board of directors and the transparency of financial statements playing a significant role in mitigating tax risk. This study suggests the need for further investigation into additional moderating factors, such as ownership structure and market pressures, as well as the incorporation of various profitability measures to gain a more nuanced understanding of the interplay between profitability and tax aggressiveness.